Tax Risks and Tax Risk Management Associated to Internal Auditing: Empirical Evidence from Greece - Boufounou, P.; Kokovidis, A.; Kounadeas, T.; Raptis, A.; Tsakas, M. (International Conference on Business and Economics - Hellenic Open University, 2025)
The goal of this paper is to highlight the importance of tax risk management in the process of creating an effective internal auditing plan. The insight of professionals (internal and external auditors, risk management consultants) is collected through online questionnaires that are analyzed to identify important correlations that affect company effectiveness of controls associated to the increasing tax risks. A regression analysis is used to determine the degree of preparation of Greek companies to deal with tax threats in accordance with their internal tax audit plan. The study concluded that companies in Greece do not plan for future tax risks but mostly deal with past incidents and “known issues”. The findings are of practical importance to companies, as their risk management departments should work closely with the internal auditors to ensure the implication of tax risk controls in their internal audit plans, especially if business development across different regions is intended. JEL Classifications: M41, M 48 Keywords: Tax Risks; Risk Management; Internal Auditing; Efficiency; Greece